Supplier selection problem in global supply chains by AHP and ANP approaches under fuzzy environment - Yucenur, G. Nilay; Vayvay, Ozalp; Demirel, Nihan Cetin (SPRINGER LONDON LTD, 2011)
In this paper, we proposed a model for selecting of the global supplier by analytical hierarchy process (AHP) and analytical network process (ANP) based on linguistic variable weight. The fuzzy AHP and fuzzy ANP methods are suggested to be a good tool for solving our proposed multiple-criteria decision-making problem. Fuzzy AHP-based methodology evaluated different decision criteria such as service quality, cost, risk factors, and supplier's characteristics involved in the selection of the best supplier in a global supply chain and ANP represented an effective tool for providing a suitable solution for managers. The linguistic levels of comparisons produced by the experts with triangular fuzzy numbers for constructing fuzzy pairwise comparison matrices. The implementation of the system was demonstrated by a problem having four stages of hierarchy which contains four criteria and 28 attributes. In conclusion, the fuzzy AHP and fuzzy ANP results were compared.
Keywords: Supplier selection; Global supply chains; Fuzzy logic; Fuzzy AHP; Fuzzy ANP; ANALYTIC NETWORK PROCESS; HIERARCHY PROCESS; INFORMATION-SYSTEMS; DECISION-MAKING; MANAGEMENT; MODEL; LOGISTICS; OPPORTUNITIES; VALIDATION; BENEFITS; Automation & Control Systems; Engineering